2008
DOI: 10.1097/pep.0b013e3181728a8c
|View full text |Cite
|
Sign up to set email alerts
|

Stretching with Children with Cerebral Palsy: What Do We Know and Where Are We Going?

Abstract: Physical therapists can consider innovative alternatives that integrate flexibility and fitness goals with community-based recreation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 28 publications
1
82
0
5
Order By: Relevance
“…30 An inverse relationship between stretching and function emerged. Formal stretching programs were reported more by participants with higher levels of impairment; this may be due to the emphasis on stretching in physical therapy sessions to delay surgery; it may also be possible that some activities reported by participants include minimal stretching components within the exercise.…”
Section: Discussionmentioning
confidence: 97%
“…30 An inverse relationship between stretching and function emerged. Formal stretching programs were reported more by participants with higher levels of impairment; this may be due to the emphasis on stretching in physical therapy sessions to delay surgery; it may also be possible that some activities reported by participants include minimal stretching components within the exercise.…”
Section: Discussionmentioning
confidence: 97%
“…[13][14][15][16][17][18][19][20][21][22][23][24] Previous studies have demonstrated that increased resistance to stretch in spastic muscle has both an active and passive component. [15][16][17][18][19][20][21][22][23][24] Dietz et al 25 provided evidence that altered mechanical properties of muscle may contribute to hypertonia in spastic patients. Some investigators have demonstrated increased passive ankle stiffness in spastic patients.…”
Section: Discussionmentioning
confidence: 99%
“…However it is more complex to complete, which suggests the MAS and ROM measures would be more effective in clinical practice. There is a lack of understanding demonstrated in general research of the theories behind contractures and stretching (Wiart et al, 2008). Therefore it is difficult to determine if the variation is from the research techniques used, body response, or a combination.…”
Section: Discussionmentioning
confidence: 99%